On the growth of Si nanoparticles in non-thermal plasma: physisorption to chemisorption conversion. (30th June 2021) - Shi, Xuetao; Elvati, Paolo; Violi, Angela
Abstract: Non-thermal plasma systems offer unique opportunities in the fields of bio-imaging, drug delivery, photovoltaics, microelectronics manufacturing. Such interests are largely inspired by the fact that hot plasma electrons coexist with neutral species and ions close to room-temperature under non-thermal plasma conditions. Modeling of these systems requires a deep understanding of the atomistic processes underlying the rich chemistry of the various radicals and ions with the nascent nanoparticle (NP) surface. A key parameter for determining the contribution of a certain radical/ion species to the NP surface growth, called sticking coefficient, is computed as a weighted sum from the simulated sticking outcomes with different collision velocities drawn from a Maxwell–Boltzmann distribution at certain temperatures. In this work, the collisions of SiH x ( x  = 1–4) fragments and silicon cluster (Si4, Si2 H6, and Si29 H36 ) surfaces, responsible for the sticking coefficients, are simulated by molecular dynamics with a reactive force field. The dependence of sticking coefficients on temperature, H coverage of both silane fragments and cluster surfaces, and the size of the cluster, are systematically examined. And the mechanism underlying the sticking events, specifically the conversion of physical aggregation to chemisorption is investigated to better understand the complex interplay between factors influencing the surface growth. The detailed and multi-parameter model of sticking coefficients, accompanied by the mechanism study of physisorption to chemisorption conversion, provides a more accurate and robust approximation of surface growth rate using sticking coefficients, and a deeper understanding of surface growth processes, for the wider non-thermal plasma simulation community.